Combination vaccine strategies to prevent enteric infections. Issue 49 (14th December 2017) - Walker, Richard; Dull, Peter
Highlights: A combined Shigella -ETEC vaccine would offer advantages for global health. Numerous candidates for Shigella and ETEC vaccines are in development. Presentation, formulation, and regulation considerations pose potential challenges. Challenges could be overcome through new vaccine candidates and techniques. Abstract: New vaccine candidates entering the current routine immunization schedule can best be accommodated as combination vaccines. A combined Shigella and enterotoxigenic E. coli (ETEC) vaccine could greatly benefit children in disease-endemic areas. New candidates are getting closer to being able to meet these needs, but they raise numerous strategic questions related to presentation, formulation, and regulatory approach. The "Combination Vaccine Strategies to Prevent Enteric Infections" workshop at the 2016 Vaccines Against Shigella and ETEC (VASE) Conference examined some of the considerations for developing such vaccines against enteric pathogens.